2014
DOI: 10.1590/s1679-45082014ao3003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of renal insufficiency in elderly cancer patients in a tertiary cancer center

Abstract: Objective To estimate the prevalence of abnormal glomerular filtration rate in elderly patients with solid tumors.Methods A retrospective study with patients aged >65 years diagnosed with solid tumors between January 2007 and December 2011 in a cancer center. The following data were collected: sex, age, serum creatinine at the time of diagnosis and type of tumor. Renal function was calculated using abbreviated Modification of Diet in Renal Disease (MDRD) formulae and then staged in accordance with the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…A study that analyzed 666 patients with solid tumors found a high prevalence of an abnormal glomerular filtration rate [39]. In another study conducted on patients with kidney failure receiving melphalan-a stomatotoxic drug used for treatment of multiple myeloma-the severity of oral mucositis increased with high-dose chemotherapy, as drug elimination was impaired due to the patients' abnormal kidney function [37].…”
Section: Discussionmentioning
confidence: 99%
“…A study that analyzed 666 patients with solid tumors found a high prevalence of an abnormal glomerular filtration rate [39]. In another study conducted on patients with kidney failure receiving melphalan-a stomatotoxic drug used for treatment of multiple myeloma-the severity of oral mucositis increased with high-dose chemotherapy, as drug elimination was impaired due to the patients' abnormal kidney function [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that renal dysfunction occur frequently in patients with cancer. 9 12 The renal insufficiency and anticancer medications (IRMA) study showed that 52.9% exhibited an estimated glomerular filtration rate (eGFR) <90 mL/min/1.73 m 2 , calculated according to the Modification of Diet in Renal Disease (MDRD) formula. Recently, a prospective population-based cohort study reported that 73.3% subjects had eGFR <75 mL/min/1.73 m 2 , on the basis of the Chronic Kidney Disease Epidemiology Collaboration equation (CKD-EPI).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular risk factors and associated comorbidities were: diabetes mellitus, arterial hypertension, dyslipidemia, obesity, thromboembolic diseases, sepsis, chronic obstructive pulmonary disease, stroke, rhabdomyolysis, congestive heart failure, myocardiopathy (ischemic and/or dilated), cardiac arrhythmia (atrioventricular block, fibrillation and/or arrhythmia), hypovolemia (hemorrhage and/or dehydration) and cardiorespiratory arrest event. Use of furosemide, non-steroidal or hormonal anti-inflammatory drugs, angiotensinogen-converting enzyme inhibitors, chemotherapeutic agents, antibiotics and vasoactive drugs were included as nephrotoxic drugs (5)(6)(7)(8) . Simultaneous antibiotic corresponded to the concomitant use of two or more drugs.…”
Section: Methodsmentioning
confidence: 99%